Bladder stone in pregnancy: a rare encounter (Nepal Medical College Journal, 2023)
Bladder stones are rare and account for approximately 5.0% of all urinary tract stones. The presence of bladder stones places the pregnancy at risk for adverse outcomes including recurrent urinary tract infections, preterm labour, and obstructed labour. Prompt and accurate diagnosis requires a high degree of suspicion and judicious use of diagnostic imaging given the higher risks of radiation exposure. Treatment ranges from conservative to more invasive approaches. Thus, management needs to be individualized to the patient with careful consideration of the potential adverse effects. We report a case of bladder stone in mid-pregnancy that was treated by open cystolithotomy.